MONETARY FINANCE ITS IMPACT ON DOMESTIC PUBLIC DEBT AND INFLATION FOR THE PERIOD (2015-2024) - Asst. Prof. Ali Abdulkadhim Dadoosh (Scholars Digest Publishing, 2025)
The implementation of monetary finance policy commenced in Iraq during 2015, marked by the Central Bank of Iraq's (CBI) discounting of treasury transfers. In 2020, substantial pressure from the Ministry of Finance (MoF) led the CBI to convert short-term debt into long-term obligations; this arrangement has persisted until the time of writing, involving annual renewals and periodic partial repayments of the transfers. Consequently, the characteristics of the MF policy in Iraq became clearly defined. Furthermore, the government (MoF) determined both the payment schedule and the interest rate. Notably, the rate, initially around (7.5%) in 2015, was reduced to (2%) after 2020 following an MoF directive, illustrating fiscal dominance over the central bank's independence. This signifies that the monetary authority financed government expenditures at reduced costs, constituting MF proper. The significance of the study relates to the contribution of monetary financing in addressing crises impacting the Iraqi economy, such as fiscal deficits and high public debt levels. Conversely, monetary financing carries significant consequences, notably inflation, if not applied judiciously and targeted towards planned real investments. An NARDL model was employed to delineate the positive and negative effects among the selected variables. The study found that MF positively aided in monetizing public debt in Iraq. However, it concurrently led to an expansion of the country's money supply, causing inflation, particularly after 2020. This necessitates careful consideration when resorting to MF, limiting its use to exceptional times and for funding the investment component of the Iraqi public budget.
Keywords: Iraqi Economy, Monetary Financing, Domestic Public Debt, Inflation, NARDL Model.